Impact of Pre-Revascularization and Post-Revascularization Cardiac Arrest on Survival Prognosis in Patients With Acute Myocardial Infarction and Following Emergency Percutaneous Coronary Intervention - Zhou, Changzuan; Lin, Qingcheng; Xiang, Guangze; Chen, Mengmeng; Cai, Mengxing; Zhu, Qianli; Zhou, Rui; Huang, Weijian; Shan, Peiren (Frontiers in Cardiovascular Medicine, 2021)
Objectives: To evaluate the effects of occurrence and timing of sudden cardiac arrest (SCA) on survival in patients with acute myocardial infarction (AMI) who underwent emergency percutaneous coronary intervention (PCI). Methods: We analyzed 1,956 consecutive patients with AMI with emergency PCI from 2014 to 2018. Patients with cardiac arrest events were identified, and their medical records were reviewed. Results: Patients were divided into non-cardiac arrest group (NCA group, n = 1,724), pre-revascularization cardiac arrest (PRCA group, n = 175), and post-revascularization SCA (POCA group, n = 57) according to SCA timing. Compared to NCA group, PRCA group and POCA group presented with higher brain natriuretic polypeptide (BNP), more often Killip class 3/4, atrial fibrillation, and less often completed recovery of coronary artery perfusion (all p < 0.05). Both patients with PRCA and POCA showed increased 30-day all-cause mortality when compared to patients with NCA (8.0 and 70.2% vs. 2.9%, both p < 0.001). However, when compared to patients with NCA, patients with PRCA did not lead to higher mortality during long-term follow-up (median time 917 days) (16.3 vs. 18.6%, p = 0.441), whereas patients with POCA were associated with increased all-cause mortality (36.3 vs. 18.6%, p < 0.001). Multivariate analysis identified Killip class 3/4, atrial fibrillation, high maximum MB isoenzyme of creatine kianse, and high creatinine as predictive factors for POCA. In Cox regression analysis, POCA was found as a strong mortality-increase predictor (HR, 8.87; 95% CI, 2.26–34.72; p = 0.002) for long-term all-cause death. Conclusions: POCA appeared to be a strong life-threatening factor for 30-day and long-term all-cause mortality among patients with AMI who admitted alive and underwent emergency PCI. However, PRCA experience did not lead to a poorer long-term survival in patients with AMI surviving the first 30 days.